2016
DOI: 10.1158/0008-5472.can-15-1625
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Hypoxic Oral Squamous Cell Carcinoma Cells Deliver miR-21 to Normoxic Cells to Elicit a Prometastatic Phenotype

Abstract: Hypoxia is a common feature of solid tumors and is associated with aggressiveness and poor patient outcomes. Exosomes, initially considered to be cellular "garbage dumpsters," are now implicated in mediating interactions with the cellular environment. However, the mechanisms underlying the association between exosomes and hypoxia during cancer progression remain poorly understood. In this study, we found that exosomes derived from hypoxic oral squamous cell carcinoma (OSCC) cells increased the migration and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
386
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(402 citation statements)
references
References 49 publications
15
386
0
1
Order By: Relevance
“…30,31 Secretory miRNAs are also involved in the remodelling of TME shaped and dominated by cancer cells. 19,32 miR-351b-and miR-210-enriched exosomes released by cancer cells increase tumour angiogenesis, thereby increasing cancer metastasis. 33 In this study, we found that exosomal miR-23a not only increases tumour angiogenesis during hypoxia, but also in normoxic conditions, suggesting that hypoxic lung cancer transmits genetic materials not only between cancer cells and endothelial cells within the hypoxic region, but also between cancer cells and distant endothelial cells located in normoxic regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Secretory miRNAs are also involved in the remodelling of TME shaped and dominated by cancer cells. 19,32 miR-351b-and miR-210-enriched exosomes released by cancer cells increase tumour angiogenesis, thereby increasing cancer metastasis. 33 In this study, we found that exosomal miR-23a not only increases tumour angiogenesis during hypoxia, but also in normoxic conditions, suggesting that hypoxic lung cancer transmits genetic materials not only between cancer cells and endothelial cells within the hypoxic region, but also between cancer cells and distant endothelial cells located in normoxic regions.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 They are capable of diffusing to neighbouring cells or being transported to distant anatomic locations where they can transduce signals or information in specific recipient cells. 18,19 Cancer-derived exosomes have been found to contribute to TME remodelling and premetastatic niche formation. 20,21 In this study, we have investigated the potential role of exosome vesicles in hypoxia-dependent signalling between lung cancer cells and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…When tumors grew to 150-200 mm 3 , nude mice were administered with an intraperitoneal injection of DDP, 4 mg/kg, twice a week. At the same time, exosomes extracted with ultracentrifugation from the culture medium were directly injected into the implanted tumors at the dose of 100 μg per mouse every 3 days for 7 times.…”
mentioning
confidence: 99%
“…MiRNA is commonly carried by exosomes and miRNA mimics are easily loaded into exosomes [49]. In many other fields, genetically engineered exosomes have been used, especially in the cancer therapy [47,[50][51][52]. Engineered exosomes in cancer therapy including drug-loading exosomes, surface-modifying exosomes, and contentmodifying exosomes [51] that may provide novel therapeutic strategies for joint diseases.…”
Section: Emerging Roles Of Exosomes In Joint Diseasesmentioning
confidence: 99%